The full damages rule principle and the limitation of the quantum respondatur for the contribution to the creditor`s damage in modern contact Law - Pérez Velázquez, Juan Pablo (CUADERNOS DE DERECHO TRANSNACIONAL, 2022)
Damage or full damages rule is the guiding principle for calculating damages. In modern Contract Law, the general rule is that the party who suffers the damages derived from the breach has the right to be placed in a position as similar as possible to that which he would have had if the contract had been executed in the agreed terms. From the foregoing, it follows that the measure, or the interest protected by compensation for damages is the interest in compliance or the creditor´s positive contractual interest. The texts of modern Contract Law (PICC, PECL, DCFR and CESL) expressly regulate the non-responsibility of the debtor for the damages suffered by the creditor to the extent that the creditor has contributed to them. In our Civil Code there is no precept that expressly includes such limitation to the amount of compensation. It has been our case law and doctrine that have tried to delimit its configuration and content through the figure called concurrence of faults or causes. The importance of the figure is not trivial since, together with the burden of avoiding or mitigating the damage and the predictability test, they configure rules of behavior that must be respected, having as their main function the delimitation of the quantum respondatur. The purpose of this paper is to analyze the anatomy of the rule, its formulation in the new Law of Contracts, as well as its foundation, function and effects on the compensation quantum.
Keywords: damages; full damages rule; expectation interest; contribution to the creditor´s damage; limitation of the quantum respondatur